Frauds, Failures and Bad Banking Decisions - Aneet (Gyan Management Journal, 2016)
The Supreme Court’s observation on February 9, 2016 (slamming bankers and the RBI for loan write-offs), while hearing a 13 year old case involving HUDCO, reveals an insensitivity to the essence ofbusiness and banking. First it was the courts, then the Parliament’s standing committee on finance and now the Central Bureau of Investigation (CBI). One hopes it won’t be the Comptroller and Auditor General (CAG) next. We are referring to the regular public bashing of bankers and the Reserve Bank of India (RBI) for the steep increase in bad loans. But it is important for the courts, investigators and public auditor to understand that the rise in the number and amount of bad loans was largely on account of the exuberance in global and Indian markets from 2004 to 2008 and the equally steady economic downturn from 2009 till date. Estimates of growth and pricing of products to capture market share during boom years may seem like instances of bad commercial judgments on hindsight, but these decisions ought not to be confused as fraud or malafide decisions. The Supreme Court’s observation on February 9 (slamming bankers and the RBI for loan write-offs), while hearing a 13 year old case involving HUDCO, reveals an insensitivity to the essence of business and banking. I loans happen in the regular course of busirn The incidence of bad loans arises wl economies go from upswing to downswinf isn’t as if bankers suddenly became corr and it is important for the courts, the me and the investigators to understand d Today, the CBI director faulted a gatherini bankers for not declaring Kingfisher a "wil defaulter in good time. Again while comment is made with good intent, barn can point to a zillion cases where i1 impossible to know when to pull the plug. do banks benefit from calling a defau "wilful".